Investigation of the avalanche ruggedness of SiC MPS diodes under repetitive unclamped-inductive-switching stress. (September 2019) - Palanisamy, S.; Ahmmed, Md.K.; Kowalsky, J.; Lutz, J.; Basler, T.
Abstract: State of the art freewheeling diodes are connected antiparallel with a switch like IGBT or MOSFET and for latter also with the internal body diode. The diodes have to be rugged enough to overcome temporary overvoltage and overcurrent conditions during transient operation. SiC merged pin Schottky (MPS) diodes are one of the superior contenders and thus it is essential to make investigations under high avalanche energy. In this work, an avalanche ruggedness of 20 A/1.2 kV SiC MPS diodes was investigated far beyond the specified maximum ratings of the device under unclamped inductive switching (UIS) measurement. The function of avalanche energy versus applied inductance was investigated under single event avalanche stress. The reliability under high repetitive avalanche energy was studied in detail. A forward voltage drift, change in the Schottky junction voltage and increase in the leakage current was observed after the high repetitive avalanche stress far beyond the safe operating area. Detailed failure analysis was made, focusing on the degradation of the metallization and possible stacking faults ( SFs ) in the SiC bulk. Furthermore, the temperature was determined as a function of the blocking voltage during avalanche stress.